Design and Simulation of Two-Wheeled Balancing Mobile Robot with PID Controller - Mudeng, Vicky; Hassanah, Barokatun; Priyanto, Yun; Saputra, Okcy (Unijourn Publisher, 2020)
Mobile transportation robots using two wheels have now been investigated. The work within this study is to design and simulate two-wheeled robots, thus it can maintain its balance. Many control methods are used to determine satisfactory control optimization, therefore a proper response is obtained by sensor recitation corresponding with the reaction of a Direct Current (DC) motor. Recently, two-wheeled transportation robot is a Segway model. In this study, we apply a Proportional Integral Derivative (PID) controller as a control system in a self-balancing robot with a working principle is similar to an inverted pendulum. In the next study, the PID controller and the whole system are applied in the microcontroller board. The angular velocity of two DC motors used as a plant can be adjusted by Pulse Width Modulation (PWM) through a motor driver. An Inertial Measurement Unit (IMU) sensor is utilized to detect the angular acceleration and angular velocity of the self-balancing robot. The phase design is constructed by planning the robot dimension, mechanical system, and an electronic system. Particularly, this study performs mathematical modeling of the robot system to obtain the transfer function. In addition, we simulate the PID parameter with multiplication between the basic parameter and several fixed constants. The simulation results indicate that the robot can maintain its balance and remains perpendicularly stable for balancing itself.